Keterampilan Guru Dalam Pengelolaan Kelas Di SD Negeri Keude Bieng Aceh Besar - Rismalia, Rismalia; Sulaiman, Sulaiman; Syafrina, Alfiati (Universitas Syiah Kuala, 2024)
This study aims to describe the skills of teachers in class management in high grades at SD Keude Bieng Aceh Besar. The approach used in this research is a qualitative approach with a descriptive research type. The subjects in this study were high school teachers at SD Negeri Keude Bieng Aceh Besar, which consisted of 3 class teachers. Data collection techniques were carried out by means of observation and interviews. Data is processed by data analysis stages, namely data reduction, data presentation, and drawing conclusions or data verification. The results of the study show that the teacher's skills in class management in high grades at SD Negeri Keude Bieng Aceh Besar have been well implemented. This can be seen from the results of observations and interviews that have been conducted by researchers indicating that the teacher has carried out classroom management in the learning process. Classroom management skills related to creating optimal learning conditions, dividing attention by the teacher visually and verbally, the teacher can also focus students' attention on learning individually or in groups and provide reinforcement to students Moderate Skills in restoring optimal learning conditions teachers still have not implemented the components of skills in restoring optimal learning conditions such as modifying behavior and finding and solving behavior that causes problems.